AN ANALYSIS OF CHANGES TO TARJIH MUHAMMADIYAH'S FATWA ON SMOKING FROM MANHAJ TARJIH'S PERSPECTIVE - Rahman, Edy Masnur (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2023)
This research aimed to reveal the approach used in the tarjih Muhammadiyah’s fatwa regarding smoking law and describe the application of legal change rules in the smoking problem from Manhaj Tarjih's perspective. This research employed literature-based with a qualitative descriptive-analysis method. The results of the research showed that smoking law Fatwa Number 30 of 2005 and Fatwa Number 7 of 2007 used three approaches, including Bayani, Burhani, and Irfani. However, the Bayani approach was still more dominant than other approaches. Fatwa Number 6 of 2010 has also used three circular approaches, namely Bayani, Burhani, and Irfani, although the Irfani approach was still felt to be lacking and has not been stated explicitly. Then, the application of the four rules for changing the law in Muhammadiyah's manhaj tarjih has been perfectly fulfilled in the case of changing the law regarding the issue of smoking in the tarjih fatwa. Therefore, the changes that occurred have been accompanied by clear arguments and did not conflict with the Al-Qur’an and as-Sunnah. It is hoped that special research from the perspective of the Irfani approach was still very lacking. Furthermore, the community is expected to be mature in responding to changes in smoking laws decided by Muhammadiyah Tarjih and Tajdid Council.